EVALUACION DEL COMPORTAMIENTO BIOLOGICO, CLINICO Y MICROBIOLOGICO DE RESINAS DE ULTIMA GENERACION - Velermoro, Victor (1999)
An study of three clases of resins of last generation was done evaluating the clinical conduct histological, microbiological and microfiltración through electronical microscopic concluting that the clinical answer in the three tippies of resins in casties of 3 mm of intensity were not present, in histologic grade you cannot see qualitive changes, in the microbiological aspect it was verified y kal the efect antimi crobianie is only produced with direct contact with the resens through the shape of an halo, with reference to the microscopic observation one of resens presented a total of a hyborderm cave.